Antimicrobial effects of new dynamic aminoglycoside derivatives - Andreieva, Iryna; Martynov, Artur; Osolodchenko, Tetyana; Zavada, Nadiya; Batrak, Olena (Annals of Mechnikov’s Institute, 2025)
Introduction. Dynamic aminoglycoside derivatives are a group of antibiotics obtained by chemical modification of aminoglycosides. Chemical changes in the aminoglycoside molecule may include modification of amino groups, sugar residues, or other parts of the molecule. Dynamic derivatives of aminoglycosides can be an important tool in the fight against bacterial infections, especially in the context of increasing antibiotic resistance. Therefore, the development of new dynamic derivatives of such antibiotics is a very urgent task of modern medicine. The aim of the work is to microbiologically substantiate the feasibility of synthesizing new dynamic derivatives of amikacin and streptomycin for use in infectious diseases. Materials & methods. The antimicrobial effect of modified derivatives of streptomycin and amikacin, which were obtained by succinic anhydride succinic acid, was investigated. Unmodified streptomycin and amikacin in isolated form were used as a comparison.For microbiological research, 6 reference and 9 clinical strains of microorganisms were used. For microbiological research, 6 reference and 9 clinical strains of microorganisms were used.The antimicrobial activity of the substances was determined by the disk and "well" methods with measurement of the diameters of the zones of inhibition of the growth of microorganisms. Results & discussion. Regarding gram-positive and gram-negative reference strains of microorganisms, the antimicrobial effect of unmodified streptomycin and amikacin by the disk method was moderate. The antimicrobial activity of succylated streptomycin against S. aureus ATCC 25923 increased to high, and against B. subtilis ATCC 6633 and reference strains of gram-negative microorganisms - within moderate limits. The antimicrobial activity of succinylated amikacin against both tested gram-positive test strains of microorganisms and the test strain E. coli ATCC 25922 increased to high. In relation to the remaining tested strains of gram-negative microorganisms, the antimicrobial activity of succylated amikacin derivatives was moderately increased. The antifungal effect against the test strain C. albicans ATCC 885-653 of both unmodified and modified forms of streptomycin and amikacin by the disk method was weak. The well method revealed high sensitivity of both unmodified and modified forms of the studied aminoglycosides to all studied reference strains of gram-positive and gram-negative microorganisms. The sensitivity of all tested clinical strains of gram-positive microorganisms (S. pneumoniae 14, S. pyogenes 2432, S. aureus 124 and E. faecalis 42) to both unmodified and modified aminoglycosides by the disk method was moderate. Among the gram-negative clinical strains studied, the sensitivity of P. aeruginosa 18 to unmodified amikacin and streptomycin when determined by the disk method was weak. Other clinical strains of gram-negative microorganisms tested (K. pneumoniae 18, E. cloaceae 17, A. baunani 150) were moderately sensitive to both unmodified aminoglycosides and modified forms. Regarding modified aminoglycosides, the sensitivity of most of the studied clinical gram-negative strains by the disk method was moderate. The antifungal activity against C. albicans of 69 unmodified aminoglycosides was weak and increased to moderate against modified forms of amikacin and streptomycin. In the well-plate study, the antimicrobial effect of streptomycin after modification against most of the clinical strains of gram-positive microorganisms studied increased from moderate to high. The sensitivity of most gram-negative clinical strains to unmodified streptomycin was moderate. The antimicrobial effect of streptomycin after modification against K. pneumoniae 18 remained unchanged (diameters of growth inhibition zones (23.3±0.5) mm), E. cloaceae 17 increased from moderate to high (diameters of growth inhibition zones from (23.3±0.5) mm to (26.0±0.0) mm) and A. baunani 150 – within moderate (diameters of growth inhibition zones from (21.3±0.5) mm to (24.7±0.5) mm). The sensitivity of P. aeruginosa 18 to streptomycin after its modification increased from weak to moderate (diameters of growth inhibition zones were (14.7±0.5) mm) and (21.3±0.5) mm, respectively). The anti-candidiasis effect of both modified and unmodified streptomycin was moderate. The sensitivity of all tested clinical strains of Gram-positive microorganisms to unmodified amikacin by the well method was moderate. The antimicrobial effect of succinylated amikacin against most of the studied clinical strains of gram-positive microorganisms increased to high. When studying the "well" method, among the gram-negative microorganisms studied, the sensitivity of most of them to unmodified amikacin was moderate. The antimicrobial effect of amikacin after modification against K. pneumoniae 18 remained almost unchanged and remained moderate. The sensitivity of E. cloaceae 17 and A. baunani 150 increased from moderate to unmodified amikacin to high to succylated amikacin. The sensitivity of P. aeruginosa 18 increased from weak to unmodified amikacin to moderate to modified amikacin. The antifungal activity of both unmodified and modified amikacin against C. albicans 69 by the well method was moderate. Conclusion. 1. When modifying streptomycin and amikacin by succinylation using both the disk and well methods, an increase in antimicrobial activity was observed against both gram-positive and gram-negative reference and clinical strains of microorganisms. 2. The results of the study indicate the prospects for further research into the antimicrobial properties of new dynamic aminoglycoside derivatives. 3. Research in this direction will allow us to propose new approaches to combating antibiotic resistance of the most common pathogens of purulent-inflammatory infections based on dynamic structures capable of self-organization based on derivatives of aminoglycoside antibiotics streptomycin and amikacin, and capable of overcoming existing resistance in microorganisms.